Cézanne - Bernabei, Roberta (Masters of art (Prestel Verlag), 2013)
This generously illustrated volume on the work of Paul Cézanne makes the world's greatest art accessible to readers of every level of appreciation. Widely regarded as the bridging link between late 19th-century Impressionism and Cubism, Cézanne's work is characterized by his intense study of his subjects. Overflowing with impeccably reproduced images, this book offers full-page spreads of masterpieces as well as highlights of smaller details, allowing the viewer to appreciate every aspect of the artist's technique and oeuvre.